Animals in love in the Andean oral tradition. The case of a worm and a young woman - Huamán Antonio, Timna Yulisa (2024)
Objective. To elucidate the traits of the characters (seductive animal and deceived maiden) and the symbolic meaning they represent within the imagination of the runa, based on a series of oral narratives known as "the animals in love." This exploration is grounded in the principles of relationality, specifically complementarity. Methodology. An interpretative analysis was conducted on a narrative collected in the province of Dos de Mayo, Huánuco (Peru). Results. Romantic relationships between a human and an animal fail due to their asymmetrical nature, which contradicts the concept of complementarity or yanantin (a fundamental condition for forming couples in the Andean context). Allegorically, it depicts a runa paired with a mana-runa, signifying the union of an ayllu (community) member with one who does not share or harmonize with the same ideological and ethical principles of the community. Conclusion. The narratives of animals in love reflect the concern to consolidate the social unity of the community through pairings that reject any foreign incursion.